OPTIMALISASI PROSES PEMBELAJARAN ANAK BERKEBUTUHAN KHUSUS: TINJAUAN TERHADAP PRAKTIK GURU DI SLB NEGERI PROF. DR. SRI SOEDEWI MASJCHUN SOFWAN, SH. JAMBI - Margaretha Tri Astuti; Yanto Yanto; Muhamad Hamdi (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2026)
The phenomenon observed in this study involved children with special needs (ABK) who frequently left the classroom to visit their parents during lessons, disrupting their learning and that of others. Some ABK were distracted by personal activities, while others often missed class altogether, hindering their ability to follow the curriculum. This study aimed to: 1) explore the role of teachers as instructors and classroom counselors in supporting ABK; 2) identify strategies to address ABK learning challenges; 3) understand ABK's perceptions of teacher support; 4) identify barriers faced by teachers; and 5) examine teachers' contributions to the goals of inclusive education. Using a qualitative descriptive approach, this study involved 11 students with mild intellectual disabilities. Data collection methods included observation, interviews, and documentation. The study findings revealed that: 1) Teachers play a significant role in providing academic, emotional, and social support while identifying ABK's needs; 2) Effective strategies include individual and group tutoring, adaptive teaching methods, and assistive technology; 3) ABK positively perceive teacher support across academic, emotional, and social domains; 4) Teachers face challenges such as managing student behavior, lack of family involvement, and limited training; 5) Teacher contributions include collaboration with parents and schools, fostering a supportive environment, and developing teaching methods.The study concluded that inclusive education in special schools (SLB) supports the learning of children with special needs. Recommendations emphasize optimizing counseling services to enhance the holistic development of children with special needs.